Digital detox : the politics of disconnecting - Syvertsen, Trine (Emerald Publishing Limited, 2020)
Social media and smartphones are criticised for being addictive, destroying personal relationships, undermining productivity, and invading privacy. In this book, Trine Syvertsen explores the phenomenon of digital detox: users taking a break from digital media or adopting measures to limit smartphone and social media use. Based on studies, documents, media texts and interviews with media users, Syvertsen discusses how media industries intensify the quest for attention, how companies and governments team up to get everybody online, and how the main responsibility for managing online risks and problems are placed on the users' shoulders. She provides a rich account of how users reduce their online engagement through time-limitations, restrictions on smartphone use, productivity apps, and use of analogue media. Syvertsen shows how digital detoxing has much in common with other forms of self-help such as mindfulness, decluttering and simple living and places digital detox within a culture of self-optimisation. But digital detox is also about sustaining face-to-face conversations, better work-life-balance, a deeper connection with nature and more meaningful interpersonal relationships. With a wealth of examples, analyses and stories, Digital Detox is a valuable guide to why digital detox and disconnection has become a topic, how it is practised, what it says about the state of media industries and how people express resistance in the 21st century.
Chapter 1: Introduction: Do we have a problem? -- Chapter 2: What is the problem? Intensifying the quest for attention -- Chapter 3: You are the problem! Everybody online and self-regulation -- Chapter 4: Managing the problem. Disconnection and detox -- Chapter 5: The problem is personal - and social: Making sense of digital detox.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Digital media -- Political aspects; Internet addiction -- Social aspects; Digital media -- Social aspects; Social Science, Technology Studies; Social interaction